2022
DOI: 10.3390/vaccines10020229
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Multi-Target Chimeric RHDV Virus-Like Particles Delivering Foreign B-Cell Epitopes

Abstract: The rabbit hemorrhagic disease virus (RHDV) vaccine platform is a nanoparticle composed of 180 copies of the viral capsid protein, VP60, self-assembled into virus-like particles (VLPs). RHDV VLPs are able to accept the simultaneous incorporation of target epitopes at different insertion sites. The resulting chimeric RHDV VLPs displaying immunogenic foreign antigens have been shown to induce specific protective immune responses against inserted heterologous T-cytotoxic and B-cell epitopes in the mouse and pig m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In addition, it has been recorded that the occurrence of the C-terminal sequence of the VP60 protein on its outer surface is responsible for the antigenic variability of these viruses [55]. It has also been demonstrated that the recombinant VP60 protein of RHD virus (now GI.1-RHDV), termed VLP (virus-like protein), does not differ morphologically and antigenically from the VP60 protein of this virus found in the environment and is used as a 'carrier' for many antigens [78,79], including as a carrier in a vaccine against GI.1a-RHDVa and GI.2-RHDV2/b viruses [14,80]. It has been shown that the high variability within the amino acid conformation of the VP60 protein of Lagovirus europaeus GI-RHDV viruses has created the possibility of distinguishing among the pathogenic RHD viruses, the antigenic variant RHDV-RHDVa, now referred to as the GI.1a-RHDVa virus, and the variant RHDV-RHDVb or RHDV2, now referred to as the GI.2-RHDV2/b virus [9,13,56], although possibly also other infectious forms, including their recombinants [4,11,54,72], and which has been the cause of the change in their infectious spectrum [6,9,10,13,14,16,19,26,[41][42][43][44][45][46][47][48][49][50][51][52]56,81].…”
Section: Lagovirus Europaeus Gi-rhdv Characteristicsmentioning
confidence: 99%
“…In addition, it has been recorded that the occurrence of the C-terminal sequence of the VP60 protein on its outer surface is responsible for the antigenic variability of these viruses [55]. It has also been demonstrated that the recombinant VP60 protein of RHD virus (now GI.1-RHDV), termed VLP (virus-like protein), does not differ morphologically and antigenically from the VP60 protein of this virus found in the environment and is used as a 'carrier' for many antigens [78,79], including as a carrier in a vaccine against GI.1a-RHDVa and GI.2-RHDV2/b viruses [14,80]. It has been shown that the high variability within the amino acid conformation of the VP60 protein of Lagovirus europaeus GI-RHDV viruses has created the possibility of distinguishing among the pathogenic RHD viruses, the antigenic variant RHDV-RHDVa, now referred to as the GI.1a-RHDVa virus, and the variant RHDV-RHDVb or RHDV2, now referred to as the GI.2-RHDV2/b virus [9,13,56], although possibly also other infectious forms, including their recombinants [4,11,54,72], and which has been the cause of the change in their infectious spectrum [6,9,10,13,14,16,19,26,[41][42][43][44][45][46][47][48][49][50][51][52]56,81].…”
Section: Lagovirus Europaeus Gi-rhdv Characteristicsmentioning
confidence: 99%
“…The self-assembly of viral structural proteins into virus-like particles (VLPs) or virus-based nanoparticles (VNPs) has gained increasing attention in recent years. These non-infectious and replication-deficient multi-subunit nanoparticles mimic the structure of native viruses ( Kirnbauer et al, 1992 ; Mohsen et al, 2020 ) and can be modified by inserting protein fragments into particle-forming proteins, resulting in versatile nanotools ( Carignan et al, 2015 ; Kalnciema et al, 2011 ; Zamora-Ceballos et al, 2022 ). Well-organized surface proteins of viral nanostructures stimulate both humoral and cellular immune responses, leading to an increased immune reaction against protein fragments displayed on nanostructures ( Mallajosyula et al, 2014 ; Ward et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Capsids of simple viruses self-assemble to package their genomes at one end of their life cycle and dissociate to release their genomes at the other end. In medicine and nanotechnology, virus-like particles (VLPs), the capsids without a genome, have seen many uses including as platforms for antigen display, as drivers of oncolysis, and as containers for enzymes, nanoparticles, and small molecules. , While there are many ways of packaging materials in a VLP, releasing the contents of the particle in a programmed manner remains a barrier, the goal of the following study.…”
Section: Introductionmentioning
confidence: 99%